The merits of insider privatization: What Russia can learn from Eastern Central Europe - Ralph P. Heinrich (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
The debate on the privatization of enterprises in Eastern Europe often presumes that enterprises are still controlled by an identifiable entity called "the state". This, however, is no longer the case. Since the demise of tight central planning, the nominally state-owned enterprises are de facto steered by insiders such as incumbent managers, workers, and local administrators. As the customary property rights of insiders are not legally acknowledged and are thus not secure, insiders tend to adopt a myopic attitude, and neglect the long-run profitability of their firms. Centrally organized privatization programs to disburse ownership rights to non-insiders are usually advocated as the best way to improve the efficiency of the firms. However, such privatization programs challenge the present position of managers, workers, and local bureaucrats. The insiders therefore tend to resist the privatization programs. If the central government cannot quickly decide the ensuing power struggle in its favor, the establishment of secure and tradable private property rights is delayed and the performance of the enterprises may deteriorate even further in the meantime. The extent to which a central government needs to take the customary property rights of insiders into account in the design and implementation of its privatization policy depends on its political power. Whereas the government in former Czechoslovakia had been able to largely disregard the claims of insiders, governments such as the Polish one have been far less successful. The evidence supports the conclusion that a weak central state is ill posed to rapidly and successfully implement privatization strategies that disregard the customary rights of insiders. In Russia and most other successor states of the Soviet Union, the central authorities are in an extremely weak position relative to enterprises and local administrations. In order to privatize quickly, Russia should largely respect and formalize the customary property rights of insiders and make these rights tradable. Although Russia's present privatization approach grants managers, workers, and local bureaucrats more say in the privatization process than the respective programs in Eastern Central Europe, Russia would be well advised to enhance the preferential conditions for insiders even further and to scale down the scope of its voucher program. The criticisms voiced against insider privatization are not convincing. They either refer to general problems of the transformation process that no privatization method could avoid, or the criticisms refer to problems that only arise if insider privatization is deemed illegal by official policies that do not take customary property rights into account and that do not make the property rights openly tradable.
Keywords: 330; Privatisierung; Eigentumsrecht; Führungskräfte; Russland; Tschechoslowakei; Polen; Ungarn